Simple process capability analysis and quality validation of monoclonal antibody production in bench-top bioreactor - Mel, Maizirwan; Arifin, Mohd Azmir; Abdul Karim, Mohamed Ismail; Yusof, Faridah (2011)
The production of monoclonal antibody (IgM) for anti-cancer by fermentation of hybridoma cell in benchtop bioreactor has been investigated. The main target of this study was to increase the percentage of cell viability and to achieve high yield of IgM. There are many ways that can be applied to improve the process and one of them is by choosing the correct Six Sigma’s Design of Experiment (DOE). In this study, Taguchi’s Experimental Design has been applied to achieve high percentage of cell viability in the fermentation experiment. The process capability of this study was later analyzed by using the MiniTab Software (Ver. 14). Analysis has shown that this study has fulfilled a minimum target of process improvement as indicated by the Cp and Cpk value of 0.90 and 0.86. This proved that the fermentation experiment has achieved cell viability of more than 80% throughout the study.